Evaluation of a training program for life skills education and financial literacy to community health workers in India: a quasi-experimental study - Shantanu Sharma; Kanishtha Arora; Chandrashekhar; Rajesh Kumar Sinha; Faiyaz Akhtar; Sunil Mehra (BMC, 2021)
Abstract Background Accredited Social Health Activists (ASHA) are community health workers responsible for improving the health status of people by facilitating their access to healthcare services. The life skills of ASHA are known to be effective in negotiating behaviour change in the community; however, there has been a meagre focus towards improving them. Considering this gap, we adopted a comprehensive training program, known as Personal Advancement and Career Enhancement (P.A.C.E.), to empower ASHAs on life skills and financial literacy. The present study intends to assess the training program in two districts of Uttar Pradesh, India, by examining changes in knowledge, perceptions, and practices of ASHAs about life skills and financial literacy. Methods We conducted a quasi-experimental, non-randomized, controlled study with pre-and post-test assessments. Data were collected on socio-demographic characteristics, knowledge, and practices related to life skills (communication skills, self-confidence, problem-solving and decision-making skills, time and stress management skills) and financial literacy. Additionally, change perceptions on gender-, life skills-, and savings-related practices at the personal, community, and workplace levels were assessed in the intervention group. Factor analysis was performed to obtain the change patterns by assessing the degree to which the four life skills, financial literacy, and change perceptions on practices were correlated. A general linear regression model was performed to assess associations among change pattern scores and socio-demographic variables. Results We analyzed the data of 171 ASHAs (intervention group:86 and control group:85). There was a significant improvement in the average post-test scores of all the life skills and financial literacy in the intervention group (p < 0.001). Three distinct change patterns were found post-training in the intervention group. Factor 1 (high loadings for change perceptions on practices) was positively associated with ASHAs aged 38 and above and with experience of ≤12 years. On the contrary, the change in financial literacy and self-confidence scores was common among ASHAs with more than 12 years of experience. Conclusions The P.A.C.E training program was found effective in improving the life skills and financial literacy of ASHAs in India.